The Pharaoh's kitchen : recipes from ancient Egypt's enduring food traditions - Mehdawy, Magda; Hussein, Amr (The American University in Cairo Press, 2010)
Judging from the evidence available from depictions of daily life on tombs and in historical texts, the ancient Egyptians were just as enthusiastic about good food and generous hospitality as are their descendants today. Magda Mehdawy and Amr Hussein have done extensive research on the cultivation, gathering, preparation, and presentation of food in ancient Egypt and have developed nearly a hundred recipes that will be perfectly recognizable to anyone familiar with modern Egyptian food. Beautifully illustrated with scenes from tomb reliefs, objects and artifacts in museum exhibits, and modern.